Impact of expected waiting time on pediatric outpatient satisfaction: a behavioral experiment study - Hui Zhang; Junhua Tian; Yu Shi; Yuping Qian; Xuan Gao; Xiaowen Zhai (BMC Health Services Research)
Abstract Background Outpatient departments of tertiary children’s hospitals in China are often overcrowded. This study used a behavioral experiment to investigate the relationship between expectations and satisfaction levels to improve visitor satisfaction. Methods The experiment consisted of control and experimental groups. Initially, the initial expected waiting times (EWT) for the subjects in both groups were obtained. Unlike the control group, subjects in the experimental group received reminders regarding waiting times and subsequently adjusted their EWT accordingly. This study mainly used non-parametric tests to analyze the differences in satisfaction levels between the two groups of subjects. Ethical approval for this study was obtained from the hospital ethics committee. Results Significant differences in satisfaction levels were observed between the control and experimental groups when AWT exceeded EWT. However, no significant disparity in satisfaction levels was observed between the two groups when the AWT was equal to or shorter than the EWT. Within the experimental group, a significant difference in satisfaction was noted during peak hours between parents effectively regulated by the EWT and those not effectively regulated. Conversely, during off-peak hours, there was no significant difference in satisfaction between those effectively regulated by the EWT and those not effectively regulated. Conclusion Providing advance notice of long waiting times can extend the EWT of the subjects and significantly enhance their satisfaction. Healthcare institutions can adjust the EWT of the visitors by informing them in advance about potential waiting times according to the temporal patterns of outpatient visitation numbers during peak hours.